Trans-anal protrusion of intussusception (TAPI) revisited: managed successfully in a resource limited hospital setting - Basu, Shouptik (International Surgery Journal, 2018)
Intussusception is the most common cause of Acute bowel obstruction in infants and toddlers. However, a Trans-anal protrusion of an intussusception (TAPI) is relatively rare and is not well reported in literature. A high index of suspicion is essential as the diagnosis is purely clinical, and often confused with rectal prolapse. Most patients present late due to neglect on the part of the parents or the primary treating physician. A late presentation usually results in a poor outcome and increased morbidity and mortality. Uncommonly these children may present early, where a prompt surgical management is desirable. The author reports a single case of a Trans anal protrusion of intussusception (TAPI) in a 1-½ -year old female child who was successfully managed in the author’s resource-limited teaching institution without a dedicated pediatric surgery unit.